Prepared: Unlocking human performance with lessons from elite sport - Gamble, P. (Informed in Sport Publishing, Coaching and Consulting, 2020)
The pursuit of human performance goes beyond sport. Whilst we might most readily associate sport with the quest to perform at the highest levels of competition, this is not exclusive to sports teams and athletes. Striving for excellence and dedication to continual improvement are hallmarks of high performing organisations, teams, and individuals across all realms. Following this logic, forward thinking individuals have started to explore processes and principles from elite sport and coaching, with the aim of applying high performance practices within their own domain. Just as there are traits that unite high performers across sectors, there are common themes and challenges shared by all those who aspire to excellence in performance. With 'Prepared' we use the lens of elite sport to illuminate universal truths and illustrate the key lessons that we can apply to our chosen domain (including sport):• the critical ingredients for a performance environment,• the dynamics of performance management at the level of the organisation, team, and individual,• the essentials of navigating the complexity of coaching humans,• the key principles and critical lessons from the process of preparing athletes for the crucible of competition, • and finally, the meta-abilities that will allow us to sustain the highest levels of performance, manage ourselves, and navigate the challenges we will inevitably face along the way. This is a book for all those who have an interest or involvement in human performance in the widest sense. Whilst the content remains highly relevant to those in sport, within the text we explore the parallels to other domains, and thereby derive unique insights for leaders, teams, and professionals in all sectors. Throughout the journey the reader is prompted to reflect and connect the dots at the culmination of each chapter to help relate the information presented to their own context.